Boundary-value problems for systems of difference equations - Boichuk О. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
Boundary-value problems for systems of difference equations with discrete argument whose linear part is the Noetherian operator are considered. The necessary and sufficient conditions of the solvability of difference boundary-value problems of this sort are obtained.